A resectorization of fire brigades in the north of Portugal - Lima, M. M.; Sousa, F.; Öztürk, E. G.; Rocha, P. F.; Rodrigues, A. M.; Ferreira, J. S.; Nunes, A. C.; Lopes, I. C.; Oliveira, C. T. (Operational Research. Springer Proceedings in Mathematics & Statistics, 2023)
Sectorization consists of grouping the basic units of a large territory to deal with a complex problem involving different criteria. Resectorization rearranges a current sectorization avoiding substantial changes, given a set of conditions. The paper considers the case of the distribution of geographic areas of fire brigades in the north of Portugal so that they can protect and rescue the population surrounding the fire stations. Starting from a current sectorization, assuming the geographic and population characteristics of the areas and the fire brigades’ response capacity, we provide an optimized resectorization considering two objectives: to reduce the rescue time by maximizing the compactness criterion, and to avoid overload situations by maximizing the equilibrium criterion. The solution method is based on the Non-dominated Sorting Genetic Algorithm (NSGA-II). Finally, computational results are presented and discussed.